(3cJGH GdQLGd (B( (3QLGd GdTjYI (B)s - (3GdMSf Hf Ydj Hf OGhO, Jbqj GdOjf, GdeYQha HGHf OGhO GdMdj,J (B740 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi habfi ddJNdi Yf GdMQcGJ GdOfjhjI s
(3GdfSNI HgG MhGTs
(3hbO JQLe GdeDda faSg ai GdcJGH ai MQa GdMGAs
(3hHChdgG Jedc ddYdGeI YHO GdbGOQ GdHZOGOi eDQN SfI (B1091(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs